2020
DOI: 10.3390/cancers12061385
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Periprostatic and Subcutaneous Adipose Tissue Lipolysis and Adipocyte Size from Men with Localized Prostate Cancer

Abstract: The prostate is surrounded by periprostatic adipose tissue (PPAT), the thickness of which has been associated with more aggressive prostate cancer (PCa). There are limited data regarding the functional characteristics of PPAT, how it compares to subcutaneous adipose tissue (SAT), and whether in a setting of localized PCa, these traits are altered by obesity or disease aggressiveness. PPAT and SAT were collected from 60 men (age: 42–78 years, BMI: 21.3–35.6 kg/m2) undergoing total prostatectomy for PCa. Compare… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 82 publications
1
15
0
Order By: Relevance
“…Five fields of the captured images were taken per slide in varying parts of the fat biopsies of each patient. Adipocytes size was measured by converting pixels into microns using Adiposoft (ImageJ) software with the following parameters: minimum diameter 10 µm, maximum diameter 1000 µm, and microns per pixel 0.439 [ 36 ] The mean adipocytes area (µm 2 ) and the number of adipocytes (per field) were determined in a blinded manner taking into account all the adipocytes of each patient’s five fields. After completing the automated analyses of the number and area of adipocytes measurements, each value was checked manually to ensure that it represented a single adipocyte to prevent errors that may have occurred during automated analyses.…”
Section: Methodsmentioning
confidence: 99%
“…Five fields of the captured images were taken per slide in varying parts of the fat biopsies of each patient. Adipocytes size was measured by converting pixels into microns using Adiposoft (ImageJ) software with the following parameters: minimum diameter 10 µm, maximum diameter 1000 µm, and microns per pixel 0.439 [ 36 ] The mean adipocytes area (µm 2 ) and the number of adipocytes (per field) were determined in a blinded manner taking into account all the adipocytes of each patient’s five fields. After completing the automated analyses of the number and area of adipocytes measurements, each value was checked manually to ensure that it represented a single adipocyte to prevent errors that may have occurred during automated analyses.…”
Section: Methodsmentioning
confidence: 99%
“…In this study, the CT-attenuation and FDG uptake of PPAT were significantly higher than those of SAT and VAT. This suggests that PPAT exhibits more prominent inflammatory and fibrotic changes than SAT and VAT in prostate cancer patients, which might be caused by the aforementioned bidirectional crosstalk between prostate cancer cells and PPAT [ 10 , 14 , 15 ]. Moreover, CT attenuation and FDG uptake of PPAT showed a positive moderate correlation, which is closer than those of SAT and VAT, indicating that the qualitative changes in PPAT could lead to changes in both CT-attenuation and FDG uptake.…”
Section: Discussionmentioning
confidence: 99%
“…PPAT is generally defined as adipose tissue that surrounds the prostate gland [ 10 , 14 ]. PPAT is often considered as a part of VAT, but it is not located within the peritoneal cavity and has different biological characteristics from VAT and SAT [ 10 , 14 , 15 ]. In vitro studies revealed that PPAT could lead to the development of prostate cancer, and crosstalk between tumor cells and PPAT cells was found to significantly contribute to the proliferation, progression, and dissemination of prostate cancer [ 10 , 14 , 16 , 17 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Adipocytes size was measured by converting pixels into microns utilizing Adiposoft (ImageJ) software with the following parameters: minimum diameter 10 µm, maximum diameter 1000 µm and microns per pixel 0.439 as previously described. [36] The mean adipocytes area (µm 2 ) and number of adipocytes (per eld) were determined in a blinded manner by taking into account all the adipocytes of the 5 elds of each patient. After completing the automated analyzes of the counting and area adipocytes measurements, each value in the data table was checked manually to ensure that it represented a single adipocyte in order to prevent errors that may occur during automated analyzes.…”
Section: Cardiometabolic Abnormalities De Nitionmentioning
confidence: 99%